Rice mutants, selected under severe drought stress, show reduced stomatal density and improved water use efficiency under restricted water conditions - Phunthong, Chutima; Pitaloka, Mutiara K.; Chutteang, Cattleya; Ruengphayak, Siriphat; Arikit, Siwaret; Vanavichit, Apichart (Frontiers in Plant Science, 2024)
Rice is among the least water-use-efficient crops, and rice plants utilise most of their water uptake for transpirational cooling via stomata. To improve water-use efficiency (WUE) in rice, reducing stomatal density and size could help optimise transpiration and photosynthesis. In this study, we compared two series of purple rice stomata mutants: the Stomatal Model Mutant (SMM) identified by microscopic observation of flag-leaf stomata (Pitaloka et al., 2022), and the Drought-selected Model Mutant (DMM) generated through screening under severe water stress.After undergoing two rounds of severe water stress between -60 to -80  m , right before the R 1-2 reproductive stage, three DMMs were selected based on their rapid recovery rate and % filledgrain percentage. Surprisingly, the three DMMs displayed 618-697 stomatal units per mm2, similar to the SMMs low-density stomata mutant (JHN 8756 (LD)). Furthermore, the four SMMs, three DMMs and the Jao Hom Nin wild type (JHN WT) were treated with two restricted water condition schemes from seedlings to harvest. The total amount of irrigation and precipitation during the experiment was 78.1 L/plant (69.1 mm/plant) for the less restricted water condition (LR) and 47.5 L/plant (42 mm/plant) for the more restricted water condition (MR). Water condition treatments had no effects on stomatal density and stomatal index. In contrast, genotypes and restricted water condition schemes affected plant height, tillers/plant, % filled grains and shoot dry weight (SDW). The three DMMs and the JHN 8756 (LD), the SMM's lowdensity stomata mutant, displayed greater resilience towards more restricted water conditions than the SMMs and the JHN wild type. Particularly, DMMs were tolerant to more restricted water condition treatments, showing no SDW penalties. Together, the DMMs and the JHN 8756 (LD) displayed higher WUE under these conditions of more restricted water conditions. Therefore, a rigorous screening process to distinguish tolerant mutants with a rapid drought recovery rate from severe water stress could pave the way to isolate more mutants with better stomatal functionality and resilience in preparation for imminent climate changes.